The Implementation of Teaching Aids in Mind Mapping Program to Improve Tarikh Islam Learning Outcomes of First Year Student at Darussalam Gontor For Girls 2 on 2020-2021 - Agus Budiman; Rahmadita Mutiah (Educan : Jurnal Pendidikan Islam, 2021)
Observations of several grade 1 students on Islamic Date learning, some students found difficulties in remembering the year of the incident, the names of Islamic historical figures, and any important points from history, therefore researchers tried to apply mind-mapping learning media in learning Islamic History to be precise KMI students. class 1E, which is an effective media to improve student learning outcome. Based on this background, this study intend: 1) To find out the increase in student activity in learning islamic history with mind mapping media for student class 1E KMI of gontor for girl 2nd campus academc year 2020-2021, and also 2) To find out the application of mind-mapping in improving the learning outcomes of islamic history for student class 1E KMI of gontor for girl 2nd campus academic year 2020-2021. In this study, The researcher used a classroom action research  collaboration (PTK) using the Kurt Lewin model which was implemented at Gontor for girl 2nd campus with a sample student class 1E of KMI. Data collection methods used are tests, observation and documentation. The study consisted of 2 cycles which included planning, implementing, observing, and reflecting. The results of this study indicate (1) the application of mind-mapping media in learning Islamic history increases student learning activeness, proven in cycle 1 to reach 77%, increase in cycle 2 to reach 90%. (2) the application of mind-mapping media is proven to be effective in improving student learning outcomes, namely reaching 38% in the first cycle and then an increase in the second cycle, namely 67%. The researcher hopes that the teacher of islamic history to apply learning media as an enhancer of student activity and achievement in accordance with the learning process and the subjects being taught.